Wildbewirtschaftung in Südwestafrika/Namibia - Bähr, Jürgen (ERDKUNDE, 1983)
In many of the world’s arid areas extensive pastoral farming has led to excessive demands upon the natural resources. In the search for ecologically adapted forms of land use discussion has recently turned increasingly to game cropping measures. The case of SWA/ Namibia serves to present a number of possibilities for increased utilisation of game. These concern especially the sale of live animals and skins, trophy hunting and the systematic cropping of game for the sale of meat. These two latter categories of utilisation in particular have recently enjoyed a great increase in intensity, so that the gross turn-over of game cropping has increased almost two-fold between 1974 and 1980. Two-thirds of this falls to the share of trophy hunting and the sale of meat (predominantly from state controlled nocturnal hunts), whereas the sale of live animals and skins has dropped to only 12% (compared to over 60% in 1974). There are at present just about 300 registered game farms in the whole country; the average number of culls in the cropping of game during the period 1979-81 was approximately 50,000 animals (pre dominantly springboks). It is to be expected that game cropping will increase still further in significance, especially in the more arid parts of the country, since the profitability of the farming economy here is already now in danger.